THE ADVANTAGES OF WTO COMMERCIAL SYSTEM - Alina HAGIU; Marinela BĂRBULESCU; Victoria Mihaela BRÎNZEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2014)
The WTO was created in 1995 with the propose to encourage and regulate trade between its member states. The primary objective of the WTO was and still is to create economic growth and encourage free trade among nations. This aspect was disputed between specialists: some say that the WTO creates economic opportunities and that its positive impact extends beyond just economic benefits by creating an international framework of political stability, offering a solid foundation for promoting international peace by encouraging good political relations among member nations and providing a solid dispute resolution process, while others say it is disfavors lower class citizens, limiting their opportunities for social and economic mobility, is only widening the global income gap between the wealthy and poor: as the rich get richer, the poor get poorer and it favors prosperous countries and multinational corporations, while preventing smaller and poorer countries from having a fair shot of engaging in open market trades and exchanges. In this paper we will stop only to emphasize the advantages of the WTO commercial system, following that in a future work to approach also the disadvantages of this commercial system.